(untitled) (Altre Modernità, 2011)
Falling Man has often been read as the tale of of an American family trying to reinstate their ordinary lives after the 9/11 attacks, and their inability to do so due to the main protagonist’s entrapment in a traumatic state. I would argue instead that Falling Man adheres to a tradition of representations of masculinity distinguished by repressed grief and prolonged adolescence. Susannah Radstone argues that the rhetorical response to 9/11 by the Bush administration is based on the opposition of two father figures: “the ’chastened’ but powerful ’good’ patriarchal father” Vs. “the ’bad’ archaic father”. She explains: “In this Manichean fantasy can be glimpsed the continuing battle between competing versions of masculinity” (2002:459) that leaves women on the margins. The battle of the fathers of Bush’s rhetoric is counterposed in Falling Man by a battle between two men that stands for an unaccomplished fatherhood. Furthermore, the dualistic vision engendered by post-9/11 rhetoric and reflected in the novel should be evaluated in a trilateral dimension, given that at its core lies a triangulation built upon three stereotypical representations: the white middle-class man; the Arab terrorist; and a composite character in the middle, the woman, who shifts from ally, to victim, to a plausible supporter of the enemy.